Establishment and implementation of an internal quality assessment program for point-of-care glucose testing at the largest public university hospital in Thailand - Jaray Tongtoyai (2018)
Participation in an external quality assessment system is a requirement of the ISO 22870:2006, which is specific for point-of-care (POC) testing. However, in the absence of external quality assessment, the ISO 22870 allows the laboratory director to alternatively establish its own internal quality assessment (IQA) program. To achieve this requirement, an IQA program for POC glucose testing was established at our hospital, in which there were 147 POC testing sites. The control samples for IQA were prepared from expired whole blood supplied by the Department of Transfusion Medicine. The stability of the glucose control sample was preserved by adding a combination of 2 antiglycolytic agents: glyceraldehydes and sodium iodoacetate. The control samples were stable for at least 8 hours. The samples were sent to all POC sites 3 times per year to evaluate the performance of POC glucose testing. The results of the analysis and comments were sent back to the POC sites, and the response rate increased. The coefficients of variation of the IQA results ranged from 4.7% to 7.9%. The number of POC sites where the results were not in the acceptable ranges and needed for corrective action was less than 6%. The IQA for POC glucose testing was successfully established and implemented at the largest public university hospital in the country. The program requires neither sophisticated equipment nor complicated procedures and provides enough volume of control materials for many POC sites. Copyright © 2012 by Lippincott Williams & Wilkins.